How did industrial land supply respond to transitions in state strategy? An analysis of prefecture-level cities in China from 2007 to 2016. (September 2019) - Zhou, Lin; Tian, Li; Gao, Yuan; Ling, Yingkai; Fan, Chenjing; Hou, Deyi; Shen, Tiyan; Zhou, Wentong
Highlights: Industrial land supply serves as a powerful tool to respond to the transitions of state strategies in China. A response bifurcation occurred in the cities of four economic-geographical regions. Except northeastern regions, the other three regions show positive response to state strategy transitions. The response of cities varies with tranditional versus high-tech industrial land supply. Abstract: Industrial land supply has long been a powerful tool for local economic growth and government competition in China. Based on Chinese prefecture-level cities' panel data from 2007 to 2016, our study investigates how industrial land supply responded to two key transitions in state strategy: the "Fiscal Stimulus Package" of 2008 and the "New-type Urbanization" and "Innovation Driven Development" of 2012. The results show that: (1) a response bifurcation of cities occurred in the four economic-geographical regions (eastern, central, western, and northeastern). The response in eastern and central regions was led by urban agglomerations, with neighbors mimicking one another. In the western region, most of the cities demonstrated an active and strong response to the two transitions. Nonetheless, it showed the characteristic of siphon effect, and local governments interacted in a zero-sum game. Meanwhile, the response of the northeastern region was not sensitive to state strategic transitions, and there was no strategic interaction among its cities. (2) We find various responses of cities at different levels of socioeconomic development. In traditional industrial land (TIL) supply, cities with higher socioeconomic levels were more adaptive to state strategic transitions. In high-tech industrial land (HIL) supply, most cities paid more attention to attracting investment in high-tech industries during the second transitional period. Among them, the smaller the economic strength of the city, the more willing it was to supply more land for high-tech enterprises. The paper concludes with implications for state strategies and regional industrial land supply policies.